Across Anthropology (Leuven University Press, 2021)
Reframing anthropology: contemporary art, curatorial practice, postcolonial activism, and museums How can we rethink anthropology beyond itself? In this book, twenty-one artists, anthropologists, and curators grapple with how anthropology has been formulated, thought, and practised ‘elsewhere’ and ‘otherwise’. They do so by unfolding ethnographic case studies from Belgium, France, Germany, Italy, the Netherlands, and Poland – and through conversations that expand these geographies and genealogies of contemporary exhibition-making. This collection considers where and how anthropology is troubled, mobilised, and rendered meaningful. Across Anthropology charts new ground by analysing the convergences of museums, curatorial practice, and Europe’s reckoning with its colonial legacies. Situated amid resurgent debates on nationalism and identity politics, this book addresses scholars and practitioners in fields spanning the arts, social sciences, humanities, and curatorial studies. Preface by Arjun Appadurai. Afterword by Roger Sansi Contributors: Arjun Appadurai (New York University), Annette Bhagwati (Museum Rietberg, Zurich), Clémentine Deliss (Berlin), Sarah Demart (Saint-Louis University, Brussels), Natasha Ginwala (Gropius Bau, Berlin), Emmanuel Grimaud (CNRS, Paris), Aliocha Imhoff and Kantuta Quirós (Paris), Erica Lehrer (Concordia University, Montreal), Toma Muteba Luntumbue (Ecole de Recherche Graphique, Brussels), Sharon Macdonald (Humboldt-Universität zu Berlin), Wayne Modest (Research Center for Material Culture, Leiden), Bonaventure Soh Bejeng Ndikung (SAVVY Contemporary, Berlin), Margareta von Oswald (Humboldt-Universität zu Berlin), Roger Sansi (Barcelona University), Alexander Schellow (Ecole de Recherche Graphique, Brussels), Arnd Schneider (University of Oslo), Anna Seiderer (University Paris 8), Nanette Snoep (Rautenstrauch-Joest-Museum, Cologne), Nora Sternfeld (Kunsthochschule Kassel), Anne-Christine Taylor (Paris), Jonas Tinius (Humboldt-Universität zu Berlin)